Cone-Beam computed tomography based evaluation of mandibular lingual foramina and incisive canal in Selected Iranian population - Mobina Tarashti Nejad; Zeinab Azizi; Mohammadreza Havasian; Maryam Tehranchi (Mashhad University of Medical Sciences, 2023)
Introduction: In order to prevent postoperative injuries in the interforaminal region, the dentist must be aware of the anatomical variations in the anterior mandible. The purpose of this study is to CBCT based evaluation of mandibular lingual foramina and incisive canal in selected Iranian population.Materials and Methods: This was a descriptive-cross-sectional study. 214 CBCT images of mandible patients referred to a private oral and maxillofacial radiology center in Tehran were examined. Prevalence and diameter of the lingual foramina, the related canal length and position of its beginning at lingual side of mandible, middle point of alveolar crest or CEJ of teeth and genial Tubercle furthermore prevalence, length and diameter of incisal mandibular canal and its position related to the inferior border, buccal and lingual cortex of mandible were measured. In addition, the effect of patient's age and gender on the measurement of anatomical dimensions was evaluated. Data were analyzed using SPSS version 24 software.Results: This study examined 83 males and 131 females. 208 (97.2percent) subjects showed the lingual foramina (LF), double MLF and double LLF predominating. 202 (94/0percent) subjects had the MIC. No significant relationship was found between diameter, location of LF and sex, as well as between diameter and length of LF channel and age (P˃0.05). While the average length of the left MIC was higher in men (P˂0.05).Conclusions: This study showed a high prevalence of LF and MIC in the selected Iranian population. Therefore, caution should be taken during the implant treatment at the anterior mandible region.